On the regulation of the expressed L-type calcium channel by cAMP-dependent phosphorylation - Zong, Xiangang; Schreieck, Jürgen; Mehrke, Gerhard; Welling, Andrea; Schuster, Angela; Bossert, Eva-Maria; Flockerzi, Veit; Hofmann, Franz (Pflügers Archiv, 1995)
The Ca2+ channel subunits α1C-a and α1C-b were stably expressed in Chinese hamster ovary (CHO) and human embryonic kidney (HEK) 293 cells. The peak Ba2+ current (IBa) of these cells was not affected significantly by internal dialysis with 0.1 mM cAMP-dependent protein kinase inhibitor peptide (mPKI), 25 μM cAMP-dependent protein kinase catalytic subunit (PKA), or a combination of 25 μM PKA and 1 μM okadaic acid. The activity of the α1C-b channel subunit expressed stably in HEK 293 cells was depressed by 1 μM H 89 and was not increased by superfusion with 5 μM forskolin plus 20 μM isobutylmethylxanthine (IBMX). The α1C-a·β2·α2/δ complex was transiently expressed in HEK 293 cells; it was inhibited by internal dialysis of the cells with 1 μM H 89, but was not affected by internal dialysis with mPKI, PKA or microcystin. Internal dialysis of cells expressing the α1C-a·β2·α2/δ channel with 10 μM PKA did not induce facilitation after a 150-ms prepulse to +50 mV. The Ca2+ current (ICa) of cardiac myocytes increased threefold during internal dialysis with 5 μM PKA or 25 μM microcystin and during external superfusion with 0.1 μM isoproterenol or 5 μM forskolin plus 50 μM IBMX. These results indicate that the L-type Ca2+ channel expressed is not modulated by cAMP-dependent phosphorylation to the same extent as in native cardiac myocytes.